Efforts to Improve Third Grade Students' Fraction Learning Outcomes Using Picture Media - Ulfa, Siti Madiah; Ainia, Carryna Zalfa; Sholikhah, Saosa Yumrotus; Siew-Eng, Ling (Journal of Action Research in Education, 2024)
A shallow understanding of fractions can impact students' learning outcomes and hinder their ability to solve more complex mathematical problems in the future. Visual media, such as images, can be an effective tool in illustrating fraction concepts visually and concretely, thus facilitating students' understanding. The aim of this research is to investigate the effectiveness of using visual media in improving the learning outcomes of third-grade students on fraction material at Tanjung Jati 2 Elementary School. Data collection techniques used in this study include tests and observations. The chosen tests are pre-tests and post-tests in the form of essay tests. The results of this study indicate that the average score in the first cycle pre-test was 61.57. In the second cycle post-test, there was an increase in students' learning outcomes with an average score of 81.31.